The orientation and mobility of visual impaired people in bus and subway networks in Brazil - Silveira, Carolina Stolf; Dischinger, Marta (Ambiente Construído, 2018)
Spatial orientation depends both on the information available in the surrounding’s environment and on the individual's ability to perceive and deal with this information. To be fully understand by its users as a transport network and, to independently move from one place to another, the urban public transport service must be able to provide accessible information where users can easily discover and reach different, and to socially engage in local activities. In Brazil, the information disposable to users is scarce and sometimes nonexistent in the urban public transport (PT), especially regarding the supply of information to everyone. This paper presents some doctoral research’s results applied in Brazil and discuss blind users’ orientation and mobility in urban public transport network. The investigation involved around two hundred blind and partially impaired users from many Brazilian regions where surveys were conducted; additionally, interviews with a focus group and the "Accompanied Walks” method. The results of the latter are here presented, showing environmental barriers and users needs.